A Comparative Analysis of the Contents of “Acid-Base Neutralization Titration” in the New and Old Editions of the Textbook Published by People’s Education Press Based on Core Competencies in China - Ma, Xiaoli; Hu, Weiping (Advances in Social Sciences Research Journal, 2023)
In the new edition of the high school chemistry textbook, published by People’s Education Press in China in 2019, the knowledge of “Acid-Base Neutralization Titration” is extracted as an independent class hour from the content of “The Application of pH” in the old edition textbook published in 2004. Based on the idea of Chinese core competencies in chemistry, the contents of “Acid-Base Neutralization Titration” in the 2019 edition and the 2004 edition of Chinese high school chemistry textbooks are compared and analyzed in this paper. It is found that the new edition of textbook is optimized in many aspects, for example, a variety of columns are set up, exercises are simplified, and the content is more concise and organized. At the same time, some suggestions are presented about the approaches to cultivating students’ core competencies and the improvement of calculation method of the examples in the new edition of textbooks.